Segment selection for fusion and artificial disc replacement in the hybrid surgical treatment of noncontiguous cervical spondylosis: a finite element analysis - Sun, Xiangyao; Huang, Jiang; Zhang, Qingming; Cao, Li; Liu, Yuqi; Song, Zelong; Tang, Wei; Sun, Siyuan; Wang, Juyong (Frontiers in Bioengineering and Biotechnology, 2024)
The treatment of skip-level cervical degenerative disease (CDD) with no degenerative changes observed in the intervening segment (IS) is complicated. This research aims to provide a reference basis for selecting treatment approaches for noncontiguous CDD. To establish accurate finite element models (FEMs), this study included computed tomography (CT) data from 21 patients with CDD (10 males and 11 females) for modeling. The study primarily discusses four cross-segment surgical approaches: upper (C3/4) anterior cervical discectomy and fusion (ACDF) and lower (C5/6) cervical disc arthroplasty (CDA), FA model; upper CDA (C3/4) and lower ACDF (C5/6), AF model; upper ACDF (C3/4) and lower ACDF (C5/6), FF model; upper CDA (C3/4) and lower CDA (C5/6), AA model. An initial axial load of 73.6 N was applied at the motion center using the follower load technique. A moment of 1.0 Nm was applied at the center of the C2 vertebra to simulate the overall motion of the model. The statistical analysis was conducted using STATA version 14.0. Statistical significance was defined as a P value less than 0.05. The AA group had significantly greater ROM in flexion and axial rotation in other segments compared to the FA group (P < 0.05). The FA group consistently exhibited higher average intervertebral disc pressure in C2/3 during all motions compared to the AF group (P < 0.001); however, the FA group displayed lower average intervertebral disc pressure in C6/7 during all motions (P < 0.05). The AA group had lower facet joint contact stresses during extension in all segments compared to the AF group (P < 0.05). The FA group exhibited significantly higher facet joint contact stresses during extension in C2/3 (P < 0.001) and C6/7 (P < 0.001) compared to the AF group. The use of skip-level CDA is recommended for the treatment of non-contiguous CDD. The FA construct shows superior biomechanical performance compared to the AF construct.